Immediate loading of dental implants in edentulous mandibles by use of Locator attachments or Dolder bars: two-year results from a prospective randomized clinical study - Kappel, Stefanie; Giannakopoulos, Nikolaos Nikitas; Eberhard, Lydia; Rammelsberg, Peter; Eiffler, Constantin (Clinical implant dentistry and related research, 2016)
Purpose The study aims to evaluate survival and incidence of complications for pairs of implants placed in the front region of edentulous mandibles and immediately loaded with either bar or Locator attachments. Materials and Methods Forty-six patients with edentulous mandibles (mean age 69.4 years at inclusion in the study; 73.9% male) received two implants in the interforaminal area of the symphysis. Dolder bar or Locator attachments, allocated randomly, were then attached immediately, and both clips and a framework were fastened to the denture by the dental technician within 72 hours. Results During the first 3 months of the 2-year period of observation, eight implants in five patients were lost, and were removed. Survival was 89.1% and 93.5% for the bar and Locator groups, respectively. During the entire period of observation, 38 prosthetic complications required aftercare. Five dentures had to be removed or reworked after implant failure, but no superstructure was lost or had to be remade for prosthetic reasons. Survival of the original dentures was 93.5% and 95.7% for the bar and Locator groups, respectively. Conclusion Within the limitations of this study, results from immediate loading of two implants in the edentulous mandible with either Locator or bar attachments hardly differed. Prosthetic complications and aftercare measures in the Locator group were frequent but easy to handle. Ease of repair and cleaning, in particular, might be reasons for choosing the single-attachment system.